Kualitas Naget Sapi yang diberi Ekstrak Daun Teh Hijau (Camellia sinensis) - Rofi Abdul Barry; Jajang Gumilar; Andry Pratama (Unpad Press, 2020)
This Green tea (Camellia sinensis) extract (GTE) contains active compouns such as tannins, flavonoids, epicatechins, catechins which have potential use as natural ingredients to improve food quality. This study aims to determine the effect of using various concentrations of GTE and determine the best concentration in terms of physical quality (water holding capacity, cooking loss and tenderness) and acceptability (taste, color, aroma, and total ecceptance) of beef nugget. The study was conducted experimentally using a Completely Randomized Design (CRD) with four treatments of beef nugget with the addition of GTE concentration 0% (P1), 2,5% (P2), 5% (P3), and 7,5% (P4). Each treatment was replicated five times. Analysis of variance was used to determine the effect of the use of GTE on the physical and acceptability quality of beef nugget. Acceptability was tested by the KruskallWallis’s test. The results showed that the addition of GTE did not give different results on physical quality and acceptability quality.